2018
DOI: 10.14256/jce.2164.2017
|View full text |Cite
|
Sign up to set email alerts
|

Management of sewage sludge – new possibilities involving partial cement replacement

Abstract: Management of sewage sludge-new possibilities involving partial cement replacement An increasing trend of sludge generation at wastewater treatment plants (WWTP) has been observed in developing countries like Croatia. Thermal processing of sewage sludge facilitates its further management, although ash is generated as new waste in the process. The proposed approach, while eliminating the need to dispose ash at non-hazardous waste disposal sites, directly reduces not only the sludge and ash disposal costs, but a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The optimum moisture content of the material with 5% of binder increased by 1%, and the bulk density decreased from 1.61 to 1.56 g/cm 3 .…”
Section: Analysis Of Results and Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The optimum moisture content of the material with 5% of binder increased by 1%, and the bulk density decreased from 1.61 to 1.56 g/cm 3 .…”
Section: Analysis Of Results and Discussionmentioning
confidence: 96%
“…Some authors have examined river sludge as bedding material in pavement bases. As a binder, they used cement with the addition of ash up to 20%, on the basis of which they concluded that ash and sludge can be used as embankments of material [3]. Many papers are related to the use of waste and recycled materials [4][5][6][7][8][9] for the production of pavement layers and with the addition of binders in order to improve the load-bearing capacity in the layer.…”
Section: Introductionmentioning
confidence: 99%
“…To create a more significant ecological effect, a push toward high-volume SCMs is inevitable [10], and involves development of binders based on SCMs with small amount of cement used as an activator [11]. To meet a growing demand for cement and concrete, and considering limited supplies of high- Research challenges for broader application of alternative binders in concrete quality SCMs, research is focussed at alternative SCMs such as red mud [11,12], biomass ash [13][14][15], copper slag, calcined clays [16], limestone [17], and their engineering combinations [18]. The main challenge is to find materials that are available in significant quantities and that have favourable chemical and physical properties (such as particle size distribution presented in Figure 1) for use as mineral addition to cement.…”
Section: High Volume Supplementary Cementitious Materials (Scm)mentioning
confidence: 99%
“…Figure 1. Comparison of size and shape of particles of (from left to rigth) cement, fly ash, biomass ash and incinirated sewage sludge ash[15,19] …”
mentioning
confidence: 99%
“…From the beginning of the 21 st century, great efforts have been made in the field of civil engineering to use recycled materials that can replace at least a portion of traditional materials, in order to ensure the greatest possible level of compliance with fundamental principles of sustainable construction industry. Thus, for instance, the use of ash obtained by burning wastewater sludge to replace a part of cement when making mortars and concrete was researched in the previous period [1]. Very encouraging results were obtained when testing the potential of using industrial by-products such as fly ash, ground masonry elements, and flotation tailing, in fabrication of the self compacting concrete (SCC).…”
Section: Introductionmentioning
confidence: 99%